The effectiveness of using newspaper articles in prewriting stage / Salemiah Abd. Ghani - Abd. Ghani, Salemiah (2003)
This study is mainly concerned with the use of newspaper articles as reading materials and brainstorming in the prewriting stage. The aim of this study is to compare the effectiveness between the use of newspaper articles and brainstorming in the prewriting activity in order to help the students to improve their writing performance. This is done by looking at the five writing components. They are content, language use, vocabulary, organization and mechanics of writing. It is found that the use of newspaper articles in the prewriting activity is effective in helping the students to improve their writing performance.